2002
DOI: 10.1128/aac.46.3.787-796.2002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Chloroquine Toxicity and Iron Acquisition in Saccharomyces cerevisiae

Abstract: Chloroquine is one of the most effective antimalarials, but resistance to it is becoming widespread. However, we do not fully understand either the drug's mode of action or the mechanism of resistance. In an effort to expand our understanding of the mechanism of action and resistance associated with chloroquine, we used Saccharomyces cerevisiae as a model eukaryotic system. To aid in the discovery of potential drug targets we applied the transcriptional profiling method to identify genes transcriptionally resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…highlights the importance of developing new antifungal compounds. Studies have shown that CQ and caspofungin exhibited synergistic activity against C. albicans, C. glabrata, Aspergillus fumigatus, and Saccharomyces cerevisiae in vitro (29), and CQ inhibited the growth of yeast species such as Histoplasma capsulatum and S. cerevisiae because of iron deprivation (17,30,31). The iron deprivation would cause a decrease in the level of membrane sterols and then cause an increase in membrane fluidity, which could enhance the passive diffusion of drugs and result in heightening drug susceptibility (32).…”
mentioning
confidence: 99%
“…highlights the importance of developing new antifungal compounds. Studies have shown that CQ and caspofungin exhibited synergistic activity against C. albicans, C. glabrata, Aspergillus fumigatus, and Saccharomyces cerevisiae in vitro (29), and CQ inhibited the growth of yeast species such as Histoplasma capsulatum and S. cerevisiae because of iron deprivation (17,30,31). The iron deprivation would cause a decrease in the level of membrane sterols and then cause an increase in membrane fluidity, which could enhance the passive diffusion of drugs and result in heightening drug susceptibility (32).…”
mentioning
confidence: 99%
“…(7,20,50). Previous studies of yeast have identified a number of cellular processes that are affected by quinoline antimalarial drugs (7,53,54). It has been shown by our group that quinidine strongly impairs potassium uptake and accumulation in yeast cells, providing a physiological advantage for cells under quinidine-induced stress (53).…”
mentioning
confidence: 85%
“…It was also demonstrated that quinidine affects the homeostasis of intracellular pH, whose main-tenance within a permissive range for the functionality of pHsensitive cellular processes is crucial to cell physiology (53,54). Another interesting study of yeast uncovered a relationship between chloroquine toxicity and iron acquisition and demonstrated that chloroquine is a competitive inhibitor of iron uptake and accumulation (7). Furthermore, genes of the iron uptake pathway are activated at the diauxic shift under the control of the Snf1 kinase (16), one of the main regulators of glucose-repressed genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Millimolar concentrations of chloroquine can prevent iron uptake in yeast (6), resulting in the upregulation of Aft1p-regulated genes and growth defects under iron-limiting conditions. The apparently opposite effect of micromolar concentrations of cryptolepine on the same regulon should have a synergistic effect, because the combination of low expression of iron-assimilating genes and prevention of iron assimilation would produce a very severe effect on the oxidative metabolism of the affected cells.…”
Section: Discussionmentioning
confidence: 99%